2008
DOI: 10.1111/j.1440-1819.2007.01775.x
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation and alexithymia among men with alcoholism

Abstract: Aim:The aim of the present study was to evaluate the relationship between alexithymia and dissociation among men with alcoholism.Methods: Participants were 176 patients consecutively admitted to the inpatient unit of a addiction treatment center. The Toronto Alexithymia Scale, the Symptom Checklist-Revised, the Dissociative Experiences Scale, the Beck Depression Inventory, the Spielberger State-Trait Anxiety Inventory, and the Michigan Alcoholism Screening Test were administered to all participants.Results: Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 40 publications
2
35
0
5
Order By: Relevance
“…Indeed, there are elevated rates of alexithymia across a multitude of psychiatric disorders including depression (Kim et al, 2008), eating disorders (Nowakowski, McFarlane, & Cassin, 2013), alcohol use disorder (Evren et al, 2008), as well as neurological disorders (Ricciardi, Demartini, Fotopoulou, & Edwards, 2015) and personality disorders (New et al, 2012).…”
Section: Alexithymiamentioning
confidence: 99%
“…Indeed, there are elevated rates of alexithymia across a multitude of psychiatric disorders including depression (Kim et al, 2008), eating disorders (Nowakowski, McFarlane, & Cassin, 2013), alcohol use disorder (Evren et al, 2008), as well as neurological disorders (Ricciardi, Demartini, Fotopoulou, & Edwards, 2015) and personality disorders (New et al, 2012).…”
Section: Alexithymiamentioning
confidence: 99%
“…At the last of 20 century, several studies have investigated the association between alexithymia and the dependence from alcohol and other substances (Taylor, Parker, Bagby 1990, Ziólkowski et al 1995, Loas, Otmani, Fremaux 1996Loas et al 2000, Farges et al 2004, De Rick, Vanheule 2007, Evren et al 2008, De Timary et al 2008, De Berardis et al 2009, De Rick etal.2009, Thorbergetal 2009). More recently, especially in the last decade, interest has shifted towards dependencies with no substances.…”
Section: Addiction and Alexithymiamentioning
confidence: 99%
“…Alexithymia, the difficulty in identifying and describing emotions, is found at increased rates among men with AUD; a study of alcohol-dependent men receiving treatment found 30% met the criteria for alexithymia. 30 Men may resort to excessive drinking as a way of coping with difficult emotions when emotional expression is not allowed or in response to emotional distress. 31,32 When experiencing negative emotions, men are more likely to show greater sensitivity to alcohol-related cues.…”
Section: Effective Interventionmentioning
confidence: 99%